The Phenomenon of Code Switching Used in Daily Communication by Young People in Tumbu Village, Karangasem - Ni Putu Novi Rupayanti (Pusat Studi Bahasa dan Publikasi Ilmiah, 2022)
The aim of this study is to find out the types and functions of code-switching that are commonly used by young people in Tumbu Village, Karangasem in their daily communication. This research is a kind of descriptive qualitative research. This study involved young people of Tumbu village, Karangasem, Bali aged 15-25 years old. The data were collected through observation and interview, and the data were analyzed descriptively. The research findings show that there was some code-switching phenomenon that happened in Tumbu Village, Karangasem. The code-switching that commonly happened in the daily communication of young people in Tumbu Village is the code-switching between the Indonesian language and the Balinese language. However, sometimes they also use or insert English words in their daily communication. The type of code-switching that is commonly used by young people in Tumbu Village, Karangasem is intra-sentential switching, which inserts words or phrases of other languages into the basic language. Moreover, the function of code-switching that is commonly used by young people in Tumbu Village, Karangasem is the Referential function, which means that people switch the language because they were more familiar with it and easier to speak certain words in the other language than their basic language.